MEMBANGUN KODE GOLAY (24, 12, 8) DENGAN MATRTKS GENERATOR DAN MENGGUNAKAN KRITERIA PERMUTASI - Irawanto, Bambang; Rizki K., Ikhsan (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT-  -One  of  the  more  useful  block  codes  k  the  binary  Q4,  .12,  8) etended  Golay  code.The  binary (24, 12,  8) actended  Golay  code  can  be  constructed  through  the  direct  sum  operationwith irwolvetwo  product codes.  This methodform the generator  matrixframework of the (24, 12, 8) Golay code  that isbasedontheso-calledTuytnorla+xlb  +xla+ b+xlcanstntction,wherea,bE  Crandxe C', C,andC',is the  (8, 4, 4) Iinear block codes.  C,  can be  gotten  through  row permutation  of the  parity submaffix  of CLWith  q  and C', and  by applying  the  generator  matrixframework  of  the  (24. 12,  S) Golry code  get  the  binary(24,  12,  8) utended Golay  code..Keyword  :Block  codes,  direct  sum,  Goloy  Code,  product codes.